Charring depth and charring rate of cross-laminated bamboo slabs exposed to a one-sided standard fire. (October 2021) - Lv, Qingfang; Wang, Weiyang; Liu, Ye
Abstract: In recent years, inspired by cross-laminated timber (CLT), cross-laminated bamboo (CLB) has been proposed to promote the development of high-rise bamboo structures. To better understand the charring properties of CLB, three groups of CLB slabs treated with different fire-resistant methods, including no treatment, painting fire-retardant coatings and impregnating flame retardants, were exposed to fire on one side with furnace temperatures following the requirements of ISO 834-1. The test results indicated that under the same fire-exposure duration, the charring degree of the CLB slabs treated with different fire-resistant methods showed a decreasing order as follows: no fire-resistant treatment > impregnating a monobasic ammonium phosphate (MAP) solution > painting fire-retardant coatings. A modified theoretical calculation method (time-location model) was proposed to calculate the charring depth considering the difference in the average charring rates between layers in which the grain direction is parallel or perpendicular to the major longitudinal direction. Furthermore, the temperature versus fire-exposure duration curves were divided into four stages: a slow rising stage, a platform stage, a rapid rising stage and a furnace temperature stage. A modified temperature profile model was proposed and was applicable for the temperature prediction of CLB slabs.